Kesulitan Guru dalam Merancang Media Inovatif Digital untuk Pembelajaran Sosiologi - Manisa Octasyavira; Nurlizawati Nurlizawati; Muhammad David Hendra (Universitas Negeri Padang, 2022)
This study aims to explain teachers' difficulties in designing innovative digital media for sociology learning. Researchers are interested in conducting this research because there are still many teachers who still experience difficulties in designing innovative digital learning media so that this makes the teaching and learning process not varied. This study used a descriptive qualitative research approach, with a case study research type, the selection of informants was carried out by purposive sampling with 7 informants namely 3 students, 2 sociology teachers, 1 school principal, 1 curriculum representative. Data collection in this study was carried out by observation, in-depth interviews, and documentation studies. Data Reduction, Data Display, and Conclusion Drawing/ Verification. The research location is SMA Negeri 2 Dumai. The results of this study indicate the difficulty of teachers in designing innovative media for sociology learning caused by internal and external factors. The internal factors included; the habit of not using the media, the ability to analyze the needs of difficult learning materials, mistakes in understanding the student center, difficulty understanding student learning styles, and not making enough use of the facilities and infrastructure provided by the school. Meanwhile, the internal factors of the teacher do not have free time to create innovative learning media.